Black and orange coloration predict success during male–male competition in the guppy. (7th October 2022) - Guerrera, Alexa G; Daniel, M J; Hughes, K A
Abstract: Investigating how intrasexual competition and intersexual mate choice act within a system is crucial to understanding the maintenance and diversity of sexually-dimorphic traits. These two processes can act in concert by selecting for the same trait, or in opposition by selecting for different extremes of the same trait; they can also act on different traits, potentially increasing trait complexity. We asked whether male–male competition and female mate choice act on the same male traits using Trinidadian guppies, which exhibit sexual size dimorphism and male-limited color patterns consisting of different colors arranged along the body and fins. We used behavioral assays to assess the relationship between color and competitive success and then compared our results to the plethora of data on female choice and color in our study population. Males initiated more contests if they were larger than their competitor. Males won contests more often if they had more black coloration than their competitor, and the effect of black was stronger when males had less orange than their competitor. Additionally, males won more often if they had either more structural color (iridescence) and more orange, or less structural color and less orange than their competitor, suggesting multiple combinations of color traits predict success. Females from our study population exhibit a strong preference for more orange coloration. Thus, traits favored in male contests differ from those favored by intersexual selection in this population. These results suggest that inter- and intrasexual selection, when acting concurrently, can promote increased complexity of sexually selected traits. Abstract : Mate choice and mate competition can favor different extremes of a trait, or different traits altogether. Female Trinidadian guppies from the Paria River prefer males with high amounts of orange color and large tail fins. Here, we show that male–male competition instead favors large males with more black and less orange on their body. The conflicting selection pressures generated by female choice and male–male competition may therefore explain the complexity of male guppy color pattern.